Female intuition in economics and conscious leadership: a comprehensive integrative review of conceptual foundations, cultural moderators, and future directions - Gómez Tobías, Roberto (Frontiers in Sociology, 2025)
BackgroundThe notion of female intuition has long been marginalized or misconstrued within economic and leadership discourse. Recent contributions from cognitive neuroscience, feminist economics, and organizational theory offer new insights into intuition as a nuanced form of embodied judgment, responsive to both ethical and contextual demands. In response to this gap, the present review systematically examines how this epistemic capacity is conceptualized, empirically explored, and shaped by institutional and cultural conditions.ObjectivesBuilding on this foundation, this analysis articulates four interrelated objectives: (1) To define and integrate the construct of female intuition within economic and leadership domains; (2) To assess its influence on innovation, risk perception, and decision quality; (3) To explore cultural, structural, and neuropsychological moderators of its expression and legitimacy; (4) To propose a multidimensional framework grounded in feminist and neuroconstructivist epistemologies.MethodsA systematic and integrative protocol was applied to peer-reviewed literature published between 2000 and 2024 across Scopus, Web of Science, PsycINFO, PubMed, and EconLit. Boolean operators and controlled vocabulary (e.g., MeSH terms, APA Thesaurus descriptors) were used to ensure precision. Eligible studies addressed intuition, leadership, or decision-making through gendered lens. Data extraction included metadata (authorship, year, country), methodology, theoretical framing, and findings. Quality appraisal followed CASP (for qualitative designs), MMAT 2018 (for mixed methods), and AMSTAR 2 (for reviews). Thematic synthesis was complemented by bibliometric mapping using VOSviewer to identify citation clusters and emerging research fronts.DiscussionBy confronting epistemic biases and expanding the discourse on intuitive cognition, this review contributes to a more inclusive understanding of leadership intelligence. Its findings offer theoretical grounding for future research, inform gender-sensitive educational practices, and support the design of economic policies that recognize cognitive diversity as a strategic asset.Systematic review registrationIdentifier: doi: 10.17605/OSF.IO/TR5DP.